Genome-wide identification of the CAD gene family and functional analysis of putative bona fide CAD genes in tobacco (Nicotiana tabacum L.) - Wu, Mingzhu; Li, Yijun; Liu, Zhengtai; Xia, Lin; Xiang, Yiyu; Zhao, Lijie; Yang, Xiaobei; Li, Zefeng; Xie, Xiaodong; Wang, Lin; Wang, Ren; Xu, Sheng; et al. (Frontiers in Plant Science, 2024)
Cinnamyl alcohol dehydrogenase (CAD) plays a crucial role in lignin biosynthesis, and the gene family encoding various CAD isozymes has been cloned and characterized in numerous plant species.However, limited information regarding CAD gene family in tobacco is currently available. In this study, we identified ten CAD genes in N. tabacum, four in N. tomentosiformis, and six in N. sylvestris.The nucleotide and amino acid sequences of these tobacco CADs demonstrate high levels of similarity, while the putative protein sequences conservatively possessed two Zn 2+ binding motifs and an NADP(H) cofactor binding motif. Both NtCAD1 and NtCAD2 had conservative substrate binding sites, similar to those possessed by bona fide CADs, and the evidence from phylogenetic analysis as well as expression profiling supported their role as bona fide CADs involved in lignin biosynthesis. NtCAD1 has two paralogous genes, NtCAD1-1 and NtCAD1-2. Enzyme activity analysis revealed that NtCAD1-1, NtCAD1-2 had a high affinity to coniferyl aldehyde, p-coumaryl aldehyde, and sinapyl aldehyde, while NtCAD2 preferred coniferyl aldehyde and p-coumaryl aldehyde as substrates. Kinetic parameters assay revealed that NtCAD1-2 functions as the most efficient enzyme. Down-regulation of both NtCAD1-1 and NtCAD1-2 resulted in reddish-brown stems without significant changes in lignin content. Furthermore, NtCAD1-1 and NtCAD1-2, and NtCAD2 showed distinct expression patterns in response to biotic and abiotic stresses, as well as different phytohormones. Our findings suggest that NtCAD1-1 and NtCAD1-2 are involved in lignin biosynthesis, with NtCAD1-2 also participating in both biological and abiotic stresses, while NtCAD2 plays a distinct role mainly in responding to biological and abiotic stresses in tobacco.